Balkan Transition (1989-2002) Turbulent Past, Promising Future - Stubos, George (Études helléniques / Hellenic Studies, 2002)
This article deals with the current economic situation in the Balkans region. Some background and the most recent data are provided to highlight the evolution of Romania, Bulgaria, Albania, Bosnia-Herzegovina, Former Republic of Yugoslavia, and FYROM (Former Yugoslav Republic of Macedonia).